Accuracy of imaging-guided biopsy in diagnosis of malignancy versus infection - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2012)
Aims: Imaging-guided biopsies obtain samples for pathologic testing in addition to therapeutic interventions in patients with cancer. Our aim was to determine the diagnostic accuracy of percutaneous biopsies of pediatric solid tumors and infectious complications of cancer treatment. Materials and Methods: This study was performed by gathering pediatric oncology patients between 1998 and 2008. A total of 41 percutaneous biopsies were performed in order to establish a diagnosis for a suspected malignancy or an infectious complication of cancer treatment. Results and Conclusions: An accurate diagnosis was achieved in 21 of 26 (87.6%) percutaneous biopsies for suspected malignancy cases or recurrence. The remaining 15 percutaneous biopsies were done for the diagnosis of infectious complications of cancer treatment with an accurate diagnosis of 60%. Imaging-guided percutaneous biopsy technique is highly accurate and safe, particularly in diagnosis of a suspected tumor.
Keywords: Imaging-guided biopsy; pediatrics; malignancy; PERCUTANEOUS BIOPSY; NEEDLE-ASPIRATION; TUMORS; LESIONS; NODULE